Analysis of the Effect of a 12-Week Sportive Recreative Program Applied on the Aged Residing in Nursing Home on Some Anthropometric and Physiological Parameters - Taşkıran, Aslı; Kaya, İsmail (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2015)
The aim of this study was to analyze the effect of a 12-week sportive recreation program applied on the aged individuals on anthropometric, physiological and physical characteristics. The 62 voluntary aged participants chosen randomly were divided into two: the experimental group of 15 males and 16 females, and the control group of 15 males and 16 females. The participants attended regular recreative activities one hour a day, three days a week. Measurements of both groups’ physical, physiological and selected motoric characteristics were taken before (Pre-RA) and after (Post-RA) the 12-week recreative activities. The data were analyzed using SPSS 17 package program and presented as mean (X) and standard deviation (SD). While evaluating the measurement results pre and post recreative program t-test was used in the dependent groups and p < 0.05 was considered significant. When the Pre-RA and Post-RA results of the aged in both groups as a result of the 12-week recreative activity program were compared, despite certain positive mathematical improvements based on the factor of individuals who had participated in the recreative activity and who hadn’t, no statistically significant difference was found between the groups’ physical, physiological and body fat percentages p>0,05. The measurement results showed positive effects of the recreative activities on the physical, physiological and body fat percentages of the individuals who had participated in them.